1/2x - 5/6x = 6
6(1/2x) - 6(5/6x) = 6(6)
3x - x = 36
2x = 36
2x/2 = 36/2
x = 36/2
x = 18
- - - - - - - - - s-
2007-02-25 06:12:12
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
4
2007-02-25 05:39:57
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
18
2007-02-25 05:41:26
·
answer #3
·
answered by beav 1
·
0⤊
0⤋
Let X be the number...
then 5X/6 - X/2 = 6...
simple algebra from here...
multiply each term by 6 to clear fractions, and get...5X-3X=36 or 2X=36...
hence X=18
2007-02-25 05:42:01
·
answer #4
·
answered by Black sea 2
·
0⤊
0⤋
Let X be the number...
then 5X/6 - X/2 = 6...
simple algebra from here...
multiply each term by 6 to clear fractions, and get...5X-3X=36 or 2X=36...
hence X=18
2007-02-25 05:40:48
·
answer #5
·
answered by Anonymous
·
2⤊
0⤋
(5/6)x - (1/2)x = 6
(5/6)x - (3/6)x = 6
(1/3)x = 6
3 * (1/3)x = 6 * 3
x = 18
2007-02-25 05:40:43
·
answer #6
·
answered by Bhajun Singh 4
·
3⤊
0⤋
Just start with:
5/6 (x) - 1/2 (x) = 6
and solve.
2007-02-25 05:45:02
·
answer #7
·
answered by Edgard L 2
·
0⤊
0⤋
18. Just do the equation, 5/6N - .5N = 6.
2007-02-25 05:41:29
·
answer #8
·
answered by th_779 1
·
0⤊
0⤋
the previous answerer was right, its 18.
2007-02-25 05:41:48
·
answer #9
·
answered by hendrix_zeppelin_stones 2
·
0⤊
0⤋
yea
2007-02-25 05:39:53
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋